2018
DOI: 10.1007/s10265-018-1071-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen and phosphorus imbalance on photosynthetic traits of poplar Oxford clone under ozone pollution

Abstract: Ozone (O 3 ) pollution and the availability of nitrogen (N) and phosphorus (P) in the soil both affect plant photosynthesis and chlorophyll (Chl) content, but the interaction of O 3 and nutrition is unclear. We postulated that the nutritional condition changes plant photosynthetic responses to O 3 . An O 3 -sensitive poplar clone (Oxford) was subject to two N levels (N0, 0 kg N ha − 1 ; N80, 80 kg N ha − 1 ), two P levels (P0, 0 kg P ha − 1 ; P80, 80 kg P ha − 1 ) and three levels of O 3 exposure (ambient conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 68 publications
2
17
0
Order By: Relevance
“…Photosynthetic fluorescence is an indicative parameter for assessing changes in the excitation energy and the status of PSII. This study showed that separate N or P addition treatment significantly increased P n max in Chinese fir during January and April, which is consistent with other studies, e.g., Zhang, et al [45]. These two key nutrients, N and P, affect the light use efficiency of PSII.…”
Section: Positive Effect Of N and P Addition On Photosynthetic Fluoresupporting
confidence: 92%
“…Photosynthetic fluorescence is an indicative parameter for assessing changes in the excitation energy and the status of PSII. This study showed that separate N or P addition treatment significantly increased P n max in Chinese fir during January and April, which is consistent with other studies, e.g., Zhang, et al [45]. These two key nutrients, N and P, affect the light use efficiency of PSII.…”
Section: Positive Effect Of N and P Addition On Photosynthetic Fluoresupporting
confidence: 92%
“…The highest AB levels were found in plants exposed to So light at I +, which, unexpectedly, showed high AB also in presence of F − and S +. These outcomes highlight that different combinations of stressors can differently, and non‐additively, affect plant growth (Landi et al, ; Pandey et al, ; Podda et al, ; Zhang et al, ). The different AB production of lettuce under variable environmental conditions did not seem due to divergent resource allocations between shoots and roots: among the factors, salinity was the most influential on AB:BB.…”
Section: Discussionmentioning
confidence: 99%
“…Leaf pigments were determined by ultra-high performance liquid chromatography (UHPLC) using a Dionex UltiMate 3000 system equipped with an Acclaim 120 C18 column (5 µm particle size, 4.6 mm internal diameter × 150 mm length) maintained into a Dionex TCC-100 column oven at 30 • C, and a Dionex UVD 170U detector (Thermo Scientific, Waltham, MA, USA; [54]. Leaf material (50 mg fresh weight, FW) was homogenized in 1 mL of 100% HPLC-grade methanol and incubated overnight at 4 • C in the dark.…”
Section: Leaf Pigmentsmentioning
confidence: 99%